Effect of Curvature of Tip and Convexity of Electrode on Localization of Particles - Ghonge, Sudarshan; Prasad, D. Nagendra; Narayan, Swarnim; Francis, Hains; Sethi, Astha; Deb, Subimal; Banerjee, Souri (Scientific Research, 2015)
We investigate the effect of curvature of the tip and the convexity of an electrode on the localization of suspended particles under the combined effect of dielectrophoresis and AC electroosmosis through simulations using COMSOL Multiphysics. A systematic analysis of the parameters defining the convexity of the electrode—the radius of the tip and the apex angle shows that suspended particles can be trapped closely to the electrode edges for comparatively larger tip radii and apex angles. This in turn should favour the trapping of polarizable molecules between the electrodes only if the fluid velocities at the vortices are not very strong.
Keywords: Finite Element Method; Transport Dynamics; AC Electro osmosis; Dielectrophoresis; Vortex